Remediation of monoethanolamine after exposure to brown coal flue gases. (November 2015) - Lim, J.; Aguiar, A.; Reynolds, A.; Pearson, P.; Kentish, S.E.; Meuleman, E.
Highlights: Remediation of MEA solutions exposed to over 50 and 1800 h of post-combustion capture. Neutralisation and CO2 stripping initially used to reduce charged amine species concentrations. Nanofiltration had low flux and rejection, but was effective in concentrating Fe. Electrodialysis was effective in removing monovalent salts. Abstract: Monoethanolamine (MEA) is the solvent most commonly considered for post-combustion capture. However, the solvent will accumulate a range of contaminants during use, notably heat stable salts, that reduce its performance. This work considers the removal of these contaminants from MEA solutions that had been exposed to over 50 and 1800 h of post combustion capture of flue gases from a brown coal-fired power station. Analysis indicated that these MEA solutions contained significant quantities of heat stable salts including iron, potassium, sulphate, nitrate and organic anions, particularly in the older sample. Both solutions were initially neutralised to free the protonated amine, which led to precipitation of some impurities within the older solvent. Nanofiltration was considered as an approach to further concentrate impurities, but was ineffective due to low permeation rates and low rejection of monovalent salts, at less than 20%. It was effective in concentrating metal contaminants and may be useful into the future for this reason. Conversely, electrodialysis was effective in removing up to 91% of the ionic content of the solutions, although the current efficiency fell at low feed conductivities. Monovalent salts such as sodium, potassium and nitrate were removed more readily than multivalent salts such as iron and sulphate. MEA loss was consistent with our prior work at around 0.15 g/m 2  s and was predominantly as the free amine rather than the carbamate salt.